Chapter Analisi lessicale degli alterati con funzione diminutiva e della varietà dei loro ruoli all'interno del Decameron - Sciarri, Gabriele (Studi e saggi, 2021)
The present article deals with the use that Boccaccio makes of diminutives in his Decameron. After a brief introduction on the lexicographic studies dedicated to the works of the author, an investigation carried out thanks to the corpus TLIO (Tesoro della Lingua Italiana delle Origini) is presented. The study is aimed at reporting the occurrences of -etto, -ello, -ino, -uccio and its variant -uzzo diminutives in their context of use in the Centonovelle. The results outline a diverse situation where these diminutives are used in a wide range of expressive situations, spanning from affective to humorous and making their use one of Boccaccio's key elements of writing style. The 'passion' for diminutives felt by the author is finally presented through a few examples of hapax legomena.